Relationship between macroeconomic indicators and investment performance of EXIM Bank Ltd. - Afridi, Md. Tasin (BRAC University, 2024)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2023.